Entrepreneurship of farmers in Poland − the current situation and development trends - Rak, Anna Maria; Multan, Ewa (Management and Administration Journal, 2024)
Currently, the economic growth in rural areas in Poland depends, to a large extent, on thedevelopment of various forms of entrepreneurship. Due to the increasing difficulties that the traditionalsectors of the rural economy are facing, the future success of rural residents is inextricably linked to thesearch for new business opportunities. They can constitute an additional source of income for farmers,as well as positively improve the living conditions of the rural population and help achieving local developmentgoals. In this study, entrepreneurship of farmers was discussed on the example of nonagriculturaleconomic activities, which is recognized as directly related to farming, i.e. using its resources(labour, land, buildings, machinery). It does not include any activity other than farming, only when labouris used as the resource of the farm to perform the work. The main objective of the study was to recognizethe scale of the phenomenon and directions of development of non-agricultural activity in Poland andmake the characteristics of the farms undertaking this type of activity.